Emotions in the parliament - parliament in emotions: a statistical approach. The project of the dictionary of the Polish parliamentary system of the 20th century (1918-2018) - Szczyszek, Michał (Papers in Linguistics, 2019)
This contribution discusses the preliminary results of research on linguistic material included in the parliamentary transcripts of the Polish parliament in 1918-2018. Parliamentary transcripts became the basis for the Polish Parliamentary Corpus (http://clip.ipipan.waw.pl/PSC) created in the Linguistic Engineering Team of the Institute of Computer Science of the Polish Academy of Sciences. This contribution presents the results of the preliminary linguistic work on this corpus: emotional tensions of randomly chosen transcripts from particular decades of the twentieth century were discussed. The summary contains information on the convergence occurring in different decades and in different periods in the history of Poland (the history of Polish parliamentarism) in the construction of parliamentary discourse - its emotionality calculated by the level of language expression.